2019
DOI: 10.1007/s00330-019-06099-7
|View full text |Cite
|
Sign up to set email alerts
|

Automated quantitative evaluation of brain MRI may be more accurate for discriminating preterm born adults

Abstract: Objective To investigate the structural brain abnormalities and their diagnostic accuracy through qualitative and quantitative analysis in term born and very preterm birth or with very low birthweight (VP/VLBW) adults. Methods: We analyzed 3T MRIs acquired 2011-2013 from 67 adults (27 term born controls, mean age 26.4 years, 8 females; 40 VP/VLBWs, mean age 26.6 years, 16 females). We compared automatic segmentations of white matter, deep grey matter and cortical grey matter, manual corpus callosum measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A previous study on a rather small subset of the present cohort investigated how well the neuroradiologist can distinguish between prematurely born adults and adults born at full-term [ 35 ]. They concluded that the discriminative power of visual inspection alone is suboptimal and can be increased by volumetric measurements.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on a rather small subset of the present cohort investigated how well the neuroradiologist can distinguish between prematurely born adults and adults born at full-term [ 35 ]. They concluded that the discriminative power of visual inspection alone is suboptimal and can be increased by volumetric measurements.…”
Section: Discussionmentioning
confidence: 99%